2008
DOI: 10.3748/wjg.14.4826
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic transection from blunt trauma associated with vascular and biliary lesions: A case report

Abstract: M a j o r i n j u r i e s o f t h e p a n c re a s m ay re s u l t i n considerable morbidity and mortality when associated with vascular and visceral injuries. In such cases, a right diagnosis and a prompt surgical intervention are necessary to give a chance to the patient. We herein describe a case of blunt abdominal trauma in a 29-yearold man whose pancreatic rupture was associated with hepatic artery, splenic vein and extrahepatic bile duct damage. Immediate surgery was performed after computer tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…These patients may have associated injury to superior mesenteric portal vein axis. Patients affected by associated vascular injuries are rarely described [5]. Bradley et al [19] reported this association in only 3 of 101 cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients may have associated injury to superior mesenteric portal vein axis. Patients affected by associated vascular injuries are rarely described [5]. Bradley et al [19] reported this association in only 3 of 101 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Increased morbidity and mortality result from associated vascular injuries and main pancreatic duct disruption [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…The hepatic lesion being the visceral lesion most commonly associated with pancreatic lesions, 19.3%, followed by the stomach, 16%, the spleen, 11%, and the colon 7.9%. Vascular lesions occupy third place among lesions accompanying pancreatic trauma: 5.5% venous (Inferior vena cava, portal vein and superior mesenteric vein) and 4.5% arterial (aorta and superior mesenteric) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%